Microbiome-based therapies for Parkinson’s disease - Alam, Mudassir; Abbas, Kashif; Mustafa, Mohd; Usmani, Nazura; Habib, Safia (Frontiers in Nutrition, 2024)
The human gut microbiome dysbiosis plays an important role in the pathogenesis of Parkinson's disease (PD). The bidirectional relationship between the enteric nervous system (ENS) and central nervous system (CNS) under the mediation of the gut-brain axis control the gastrointestinal functioning. This review article discusses key mechanisms by which modifications in the composition and function of the gut microbiota (GM) influence PD progression and motor control loss. Increased intestinal permeability, chronic inflammation, oxidative stress, α-synuclein aggregation, and neurotransmitter imbalances are some key factors that govern gastrointestinal pathology and PD progression. The bacterial taxa of the gut associated with PD development are discussed with emphasis on the enteric nervous system (ENS), as well as the impact of gut bacteria on dopamine production and levodopa metabolism. The pathophysiology and course of the disease are associated with several inflammatory markers, including TNF-α, IL-1β, and IL-6. Emerging therapeutic strategies targeting the gut microbiome include probiotics, prebiotics, synbiotics, postbiotics, and fecal microbiota transplantation (FMT). The article explored how dietary changes may affect the gut microbiota (GM) and the ways that can affect Parkinson's disease (PD), with a focus on nutrition-based, Mediterranean, and ketogenic diets. This comprehensive review synthesizes current evidence on the role of the gut microbiome in PD pathogenesis and explores its potential as a therapeutic target. Understanding these complex interactions may assist in the development of novel diagnostic tools and treatment options for this neurodegenerative disorder.